Nomens for Designation of Persons in the Ukrainian Media Discourse - Navalna, Maryna; Kostusiak, Nataliia; Mezhov, Oleksandr; Sovtys, Nataliia; Khomych, Tetiana; Hlushych, Valentyna; Adakh, Nataliia; Pryimachok, Oksana; Skliarenko, Olesia; Holoiukh, Larysa (My University, 2024)
The article analyzes the nomens of the period of the Russian-Ukrainian war (2022-early 2024) based on the language material of modern Ukrainian mass media. The study of the texts of the most popular Ukrainian mass media resources made it possible to identify the main nomens used to designate persons, which were actualized as a result of extraneous factors, in particular, the war and the negative consequences it caused. It was possible to classify the nomens lexicon for designation of persons, in particular, the substantive units recorded in the language of modern Ukrainian mass media, to determine the lexical-grammatical and functional load of these nomens. During the research, the following methods were used: descriptive, which made it possible to inventory, systematize, and classify terms selected from mass media texts; by the method of complex analysis, which contributed to the analysis of lexical units in the lexical-grammatical aspect; the method of contextual semantic analysis, used to study nomens to designate persons with an emphasis on the intratextual environment; the method of component analysis - in order to reveal the semantic features of lexical units.
Keywords: nomen; vocabulary; lexeme; media; discourse; extra-linguistic factors; war; functionality; colloquialism; negative evaluation